Late effects of children following cancer therapy - Wawryków, Agata; Korabiusz, Katarzyna; Stecko, Monika Joanna; Janik, Inga; Sawicka, Karolina; Wawryków, Paweł; Harasimowicz, Joanna (Journal of Education, Health and Sport, 2018)
In recent years, thanks to the significant progress in medicine, about 75% of children are successfully treated of malignancies. Due to very intensive methods of therapy, anti-cancer treatment is associated with the high risk of complications - both early and late. The paper presents the long-term consequences of cancer treatment in childhood.